Análise da atividade : criações em trottoir estrelando as noivinhas do Parque Moscoso - Mattedi, Ana Paula da Vitoria (2013)
In this research we analyse the activity of the sex workers of Parque Moscoso, ES/Vitória, Brazil. For its development, we use the concept of activity formulated by a French linage of studies on the field of labour – the Ergology and the Clinic of Activity (Clinique de l'Activité) -, and the methodology of the Instructions to the Ringer. The analyses on the technologies of power, from the readings of Michel Foucault, also permeate throughout the extent of the dissertation. Especially when we think about the spatial configuration of the cities and of these women in the cities, as well as in the construction of the female and prostitute images as being contraries. This work aims not to accept or reject prostitution, but to put forth contemporary questions that constitute it in analysis, probing them.